Pharyngo-Esophageal Perforation Following Anterior Cervical Spine Surgery: A Single Center Experience and a Systematic Review of the Literature. Issue 4 (May 2022) - Moletta, Lucia; Pierobon, Elisa Sefora; Salvador, Renato; Volpin, Francesco; Finocchiaro, Francesco Massimiliano; Capovilla, Giovanni; Piangerelli, Alfredo; Ciccioli, Eleonora; Zanchettin, Gianpietro; Costantini, Mario; Merigliano, Stefano; Valmasoni, Michele
Study Design: Case series and systematic review of the Literature. Objectives: Pharyngo-esophageal perforation (PEP) is a rare, life-threatening complication of anterior cervical spine surgery (ACSS). Best management of these patients remains poorly defined. The aim of this study is to present our experience with this entity and to perform a systematic Literature review to better clarify the appropriate treatment of these patients. Methods: Patients referred to our center for PEP following ACSS (January 2002-December 2018) were identified from our database. Moreover, an extensive review of the English Literature was conducted according to the 2009 PRISMA guidelines. Results: Twelve patients were referred to our Institution for PEP following ACSS. Indications for ACSS were trauma (n = 10), vertebral metastases (n = 1) and disc herniation (n = 1). All patients underwent hardware placement at the time of ACSS. There were 6 early and 6 delayed PEP. Surgical treatment was performed in 11 patients with total or partial removal of spine fixation devices, autologous bone graft insertion or plate/cage replacement, anatomical suture of the fistula and suture line reinforcement with myoplasty. Complete resolution of PEP was observed in 6 patients. Five patients experienced PEP persistence, requiring further surgical management in 2 cases. At a median follow-up of 18.8 months, all patients exhibited permanent resolution of the perforation. Conclusions: PEP following ACSS is a rare but dreadful complication. Partial or total removal of the fixation devices, direct suture of the esophageal defect and coverage with tissue flaps seems to be an effective surgical approach in these patients